Quality of education and its role in eliminating gender barriers in Kazakhstan - Kireyeva, A.; Kenzheali, Y. (Karagandy University of the name of academician E.A. Buketov, 2025)
Improving the quality of education and achieving gender equality are considered key conditions for sustainable social and economic development. The study aims to identify the factors influencing gender inequality in Kazakhstan, with an emphasis on the role of the education system in ensuring equal access and reducing differences in the labor market. The study’s methodological framework included four stages and relied on quantitative and qualitative data analysis. The quantitative part is based on national statistics data for 2008–2024 and the results of a questionnaire survey of 104 respondents. The qualitative study included the interpretation of individual responses and an assessment of the perception of educational processes. In the first stage, flexplot visualization displayed the data structure and trends. In the second stage, principal component analysis was conducted to reduce the dimensionality of the data and highlight key factors. The third stage was multiple regression analysis aimed at quantitatively assessing the impact of investments in education, digital infrastructure, and economic activity on the level of gender inequality. In the fourth stage, a substantive analysis of the perception of the quality of education and its connection with ideas about equality was carried out. Thus, investments in education and professional development contribute to reducing gender differences, while digital connectivity did not demonstrate a statistically significant impact. Most importantly, educational opportunities and quality teaching were identified as key factors. Moreover, the results revealed that public expectations of the role of education are based on availability and quality of education. Education is expected to remove sociocultural barriers and regional disparities and comply with the labor market requirements.
Keywords: education; gender equality; quality; government; digitalization; labor market; tertiary education; Kazakhstan